DAYA TERIMA MASYARAKAT PADA SELAI WANI (MANGIFERA CAESIA) SEBAGAI DIVERSIFIKASI PANGAN - Ida Bagus Satria Harta Widana; Risa Panti Ariani; Cokorda Istri Raka Marsiti (Jurnal Pendidikan Teknologi dan Kejuruan, 2026)
Wani fruit (Mangifera caesia) is a seasonal fruit endemic to Bali with high nutritional and economic value. However, its postharvest shelf life is relatively short, lasting only 4–5 days after ripening, which often results in significant postharvest losses. This study aimed to: (1) develop a formulation for wani fruit jam based on the literature on tropical fruit jam processing, and (2) evaluate consumer acceptability of the jam in terms of color, aroma, taste, and texture. The study employed a laboratory experimental method using a One-Shot Case Study design. The research object was wani fruit jam formulated with 400 g of fruit pulp, 60 g of granulated sugar, 100 mL of water, and 10 g of lemon juice. The formulation was developed through preliminary trials and standard tropical fruit jam ratios. The study involved 50 untrained panelists, consisting of students from Universitas Pendidikan Ganesha, who evaluated the product using a five-point hedonic scale. Data were analyzed using descriptive quantitative methods by calculating the mean score for each sensory attribute. The results indicated that the wani fruit jam achieved a "Highly Liked" category for all evaluated attributes, with mean scores of 4.18 for color, 4.14 for aroma, 4.24 for taste, and 4.02 for texture. The variation in scores among sensory attributes represented normal differences in panelists' perceptions, while all attributes consistently fell within the "Highly Liked" category. The slow-cooking process for 45 minutes was effective in preserving the fruit's natural characteristics. It can be concluded that wani fruit jam demonstrated a high level of consumer acceptability among the tested participants and has strong potential for further development as a preserved fruit product. Nevertheless, this study was limited by the demographic scope of the panelists and the absence of physicochemical and microbiological analyses. Therefore, future studies are recommended to conduct comprehensive shelf-life evaluations supported by physicochemical and microbiological assessments.